Dissemination and evaluation of the ASAS/EULAR recommendations for the management of ankylosing spondylitis: results of a study among 1507 rheumatologists. Issue 6 (29th November 2007) - Gossec, L; Dougados, M; Phillips, C; Hammoudeh, M; de Vlam, K; Pavelka, K; Pham, T; Braun, J; Sieper, J; Olivieri, I; van der Heijde, D; Collantes, E; et al.
Abstract : Background: Ten ASAS/EULAR recommendations for the management of ankylosing spondylitis (AS) were published in 2006. Objectives: ( a ) To disseminate and ( b ) to evaluate conceptual agreement with, and ( c ) application of, these recommendations as well as ( d ) potential barriers to the application. Methods: A questionnaire was sent to rheumatologists in 10 countries. It included ( a ) the text of the recommendations; ( b ) rheumatologists' demographic variables; ( c ) two numerical rating scales from 1 to 10 for each recommendation: conceptual agreement with, and application of, the recommendation (10 indicates maximal agreement and maximal application); and ( d ) a list of potential barriers to the application of the recommendation. Statistical analysis included descriptive and multivariate analyses. Results: 7206 questionnaires were sent out; 1507 (21%) were returned. Of the 1507 answering rheumatologists, 62% were men, mean (SD) age 49 (9) years, and 34% had an academic position. Conceptual agreement with the recommendations was high (mean (SD) for all recommendations 8.9 (0.9)). Self-reported application was also high (8.2 (1.0)). The difference between agreement and application varied across recommendations and countries. The most pronounced discrepancies were reported for use of anti-tumour necrosis factor drugs in a few countries, with funding as the most commonly reported barrier for application of this recommendation. Conclusion: This large project has helped the dissemination of the ASAS/EULAR recommendations for the management of AS and shows that conceptual agreement with the recommendations is very high. The project also highlights inequalities in access to healthcare for European citizens with AS.